Engineering the acceptor substrate specificity in the xyloglucan endotransglycosylase TmXET6.3 from nasturtium seeds (Tropaeolum majus L.) - Stratilová, Barbora; Firáková, Zuzana; Klaudiny, Jaroslav; Šesták, Sergej; Kozmon, Stanislav; Strouhalová, Dana; Garajová, Soňa; Ait-Mohand, Fairouz; Horváthová, Ágnes; Farkaš, Vladimír; Stratilová, Eva; Hrmova, Maria (Plant molecular biology, 2019)
KEY MESSAGE: The knowledge of substrate specificity of XET enzymes is important for the general understanding of metabolic pathways to challenge the established notion that these enzymes operate uniquely on cellulose-xyloglucan networks. Xyloglucan xyloglucosyl transferases (XETs) (EC 2.4.1.207) play a central role in loosening and re-arranging the cellulose-xyloglucan network, which is assumed to be the primary load-bearing structural component of plant cell walls. The sequence of mature TmXET6.3 from Tropaeolum majus (280 residues) was deduced by the nucleotide sequence analysis of complete cDNA by Rapid Amplification of cDNA Ends, based on tryptic and chymotryptic peptide sequences. Partly purified TmXET6.3, expressed in Pichia occurred in N-glycosylated and unglycosylated forms. The quantification of hetero-transglycosylation activities of TmXET6.3 revealed that (1,3;1,4)-, (1,6)- and (1,4)-β-D-glucooligosaccharides were the preferred acceptor substrates, while (1,4)-β-D-xylooligosaccharides, and arabinoxylo- and glucomanno-oligosaccharides were less preferred. The 3D model of TmXET6.3, and bioinformatics analyses of identified and putative plant xyloglucan endotransglycosylases (XETs)/hydrolases (XEHs) of the GH16 family revealed that H94, A104, Q108, K234 and K237 were the key residues that underpinned the acceptor substrate specificity of TmXET6.3. Compared to the wild-type enzyme, the single Q108R and K237T, and double-K234T/K237T and triple-H94Q/A104D/Q108R variants exhibited enhanced hetero-transglycosylation activities with xyloglucan and (1,4)-β-D-glucooligosaccharides, while those with (1,3;1,4)- and (1,6)-β-D-glucooligosaccharides were suppressed; the incorporation of xyloglucan to (1,4)-β-D-glucooligosaccharides by the H94Q variant was influenced most extensively. Structural and biochemical data of non-specific TmXET6.3 presented here extend the classic XET reaction mechanism by which these enzymes operate in plant cell walls. The evaluations of TmXET6.3 transglycosylation activities and the incidence of investigated residues in other members of the GH16 family suggest that a broad acceptor substrate specificity in plant XET enzymes could be more widespread than previously anticipated.
Keywords: Base Sequence; Germination; petržel (rod); proteinové inženýrství; Glycosylation; Seeds; Substrate Specificity; semena rostlinná; sekvence aminokyselin; Plant Proteins; strukturní homologie proteinů; Glycosyltransferases; Amino Acid Sequence; komplementární DNA; rostlinné proteiny; Petroselinum; Models, Molecular; Phylogeny; molekulární modely; glykosylace; glykosyltransferasy; sekvence nukleotidů; Protein Engineering; Tropaeolum; DNA, Complementary; substrátová specifita; fylogeneze; klíčení; Structural Homology, Protein